Time Dependence of Elimination of Different PEth Homologues in Alcoholics in Comparison with Social Drinkers. (29th October 2013) - Gnann, Heike; Thierauf, Annette; Hagenbuch, Friedemann; Röhr, Bernhard; Weinmann, Wolfgang
<x xml:space="preserve">Abstract</x> Background Phosphatidylethanol (PEth) is a direct marker of alcohol consumption, which has been known for almost 30 years. Each PEth molecule carries 2 fatty acids, which differ in chain length and degree of unsaturation. It is formed by means of phospholipase D in the presence of ethanol. Usually, this marker was used by quantification of the PEth homologue 16:0/18:1. The intention of this work was to get more information about the distribution and the quantity of the different PEth homologues. Methods Blood samples from 12 alcohol‐dependent subjects were collected and analyzed during withdrawal therapy. For comparison, blood from 78 healthy social drinkers was also analyzed. PEth analysis was performed as follows: after liquid–liquid extraction, the homologues were separated on a Luna Phenyl Hexyl column, injected to an HPLC system (1100 system; Agilent) and identified by ESI‐MS/MS (QTrap 2000; AB Sciex) using multiple reaction monitoring. Results PEth 16:0/18:1 is the major homologue comparing the area ratios of PEth homologues in blood samples from alcoholics. Additional prevalent homologues were PEth 16:0/18:2, 18:0/18:2, and 18:0/18:1. The homologues occurring in blood samples from alcoholics as well as from social drinkers were mostly the same, but differences among their distribution pattern were observed. Conclusions In addition to the approach to quantitate the PEth homologue 16:0/18:1, this is a new and alternative proceeding for the differentiation between alcoholics and social drinkers using this alcohol consumption marker.